Phantom phone signaling (PPS) and mental health - a review - Soroka, Kamil; Samardakiewicz-Kirol, Emilia; Szawłoga, Tomasz; Styk, Wojciech; Samardakiewicz, Marzena (Current Problems of Psychiatry, 2024)
Introduction: The common usage of mobile phones, with an estimated number of 7.26 billion users, raises the question about their impact on health and daily life. Significant problems with the use of mobile phones are hearing phantom ringing (PR), phantom vibration (PV), or phantom blinking (PB), which collectively refer to phantom phone signaling (PPS). The following systematic review aimed to gather existing knowledge in PRS and PVS phantom phone signaling to identify potential new research areas. The PRISMA systematic review aimed to gather existing knowledge in PRS and PVS phantom phone signaling to identify potential new research areas.Methods: The literature search was conducted using Pubmed, Web of Science, Scopus, EBSCO, and Google Scholar databases to retrieve publications up to March 3, 2023. An additional search was performed in January 2024. The selection conditions were met by 34 articles that analyzed demographic and psychological factors.Results: The phenomenon of PR, PV, or PPS in general is inversely correlated with the age of the respondents. The results indicate that the number and intensity of perceived PV are related to where the person carries the phone. Educational or communication purposes of phone use are associated with the experience of PPS. The literature also indicates a correlation between phoneaddiction and PV, PR, and PPS in general and between depression and, anxiety and phantom experiences.Discussion: The PPS is a phenomenon that appears to be related to addiction. Future research is worth to be conducted on other and larger research groups. Additionally, longitudinal research could be considered.